THE SHOPAHOLIC LIFESTYLE IN SOPHIE KINSELLA THE SECRET DREAMWORLD OF A SHOPAHOLIC - Makalew, Gloria Aprilli; Rorintulus, Olga; Kamagi, Sarah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The study aims to reveal the shopaholic lifestyle of the character Rebecca in Sophie Kinsella’s The Secret Dreamworld of a Shopaholic. In conducting this research the writer uses qualitative research. Qualitative research involves the data collected are in the form of words rather than numbers. And in analyzing the data, the writer uses a psychological approach. The data collected in this research are from two sources, primary and secondary sources. A primary source is novel itself by Sophie Kinsella’s The Secret Dreamworld of a Shopaholic and secondary sources are the other books and data from internet that related to this research. This study focuses on looking at the shopaholic type based on the types proposed by Ronny F. Ronodirdjo and also finding the causes and the effects feel by a shopaholic based on Rebecca's story. And the results of the study show that Rebecca's shopaholic lifestyle is more prominent in the shopaholic image hunter type because Rebecca tries to show a good self-image for those around her. And the cause for her being shopaholic is caused by the influence of her family and social environment. And the effect this makes herself a materialistic person and stuck with a fashion victim and not only that, in the end she was trargped with debt.